Skills, Identity, and Power: The Multifaceted Concept of Language Diversity - Church-Morel, Amy; Bartel-Radic, Anne (Management international / International Management / Gestiòn Internacional, 2016)
The study of the multilingual character of multinational companies has grown into a legitimate field of research in international business. This paper provides a conceptualization of one of the central notions in this field: language diversity. We do this by relating the notion of language diversity to the concept of diversity in three dimensions: variety, separation or disparity. Our theoretical contribution is illustrated and further elaborated through a case study of multilingual team collaboration in the software industry. This paper explores the theory-building potential of stronger connections between diversity scholarship and the language research stream in international business.